A quantitative study of Chinese learners’ identities as reflected in their attitudes toward English accents - Yan, Huang; Azirah Hashim, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Once an asset owned exclusively by native English speakers (NESs) in inner circle, the native English speaking norms, specifically the standard varieties of British and American English, have been taken for granted as models for non-native English speakers (NNESs) in outer and expanding circles to imitate and approximate to. But this paradigm is under severe attack given the fact that people who use English as a lingua franca (ELF) have far outnumbered NESs. This paper aims to show how Chinese tertiary-level second language (L2) learners perceive different English accents and how their perceptions were related to their identities within the framework of ELF. By means of an online questionnaire survey, data from 574 English major students were retrieved and analysed with the assistance of SPSS 20.0 and Nvivo 11.0. The current study focuses on ambivalence in respondents’ attitudes toward different English accents. On the one hand, there was an obvious bias towards NES norms and accents and a strong bias against Chinese-accented English and other NNES accents; on the other hand, there was an emergence of linguistic rights and learner identity experienced by some respondents, which demonstrated itself in highlighting pragmaticity in communication, endorsing L1-accented Chinese identity, and questioning benchmark roles accorded to NES accent standards. The implication of the current study is to acknowledge an urgency of addressing the controversies between the linguistic reality and the prescriptive standards, and between the respondents’ hidden appeals for projecting their identity via L1-accented English and highly-acclaimed NES accent models.